2008
DOI: 10.4012/dmj.27.75
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Resin-based Root Canal Filling Materials with K3 Rotary Instruments: Relative Efficacy for Different Combinations of Filling Materials

Abstract: Removal of resin-based root canal filling materials may cause serious problems during root canal retreatment. This study compared the working time and amount of canal enlargement when different resin-based root canal filling materials were removed with K3 rotary instruments with or without heat-softening using System B. Root canal sealer/filling point combinations tested were Epiphany/Resilon, SuperBond/Resilon, SuperBond/gutta-percha, and Canals N/gutta-percha. The materials were filled into simulated curved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
3
10
0
1
Order By: Relevance
“…Recently, nickel-titanium (Ni-Ti) rotary instruments are used for removing root canal fillings (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and specially designed instruments, such as ProTaper Retreatment Files (Dentsply Maillefer, Ballaigues, Switzerland), have been developed (24,26,29,31,32). Ni-Ti rotary instruments are also used for removing Thermafil plastic carriers (16,20,25); Thermafil Plus uses a grooved carrier to facilitate its removal by providing an access point for these instruments (33).…”
mentioning
confidence: 99%
“…Recently, nickel-titanium (Ni-Ti) rotary instruments are used for removing root canal fillings (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and specially designed instruments, such as ProTaper Retreatment Files (Dentsply Maillefer, Ballaigues, Switzerland), have been developed (24,26,29,31,32). Ni-Ti rotary instruments are also used for removing Thermafil plastic carriers (16,20,25); Thermafil Plus uses a grooved carrier to facilitate its removal by providing an access point for these instruments (33).…”
mentioning
confidence: 99%
“…18,17,136 An advantage of Resilon is that it can be removed in a similar manner to gutta-percha (Table 4). [137][138][139][140][141][142][143][144][145][146][147][148][149][150] A series of studies have compared the removal of Resilon to guttapercha with the time taken for removal and residual material remaining the main variables investigated. Most studies have concluded that Resilon is readily removable using a variety of techniques.…”
Section: Removal Of Resilonmentioning
confidence: 99%
“…To properly remove the gutta-percha obturating material, many techniques and materials have been used in root canal-treated teeth. These include K-files or H-files, heat-carrying instruments, chemical solvents, ultrasonic instruments, engine driven rotary files such as Gates Glidden drill, GPX gutta-percha remover, NiTi rotary instruments, retreatment files (R-Endo, ProTaper and Mtwo retreatment files) heat carrier tips, ultrasonic files and lasers 2,[9][10][11] . The ProTaper retreatment file system (DentsplyMaillefer, Ballaigues, Switzerland) includes three retreatment instruments which are various tapers and diameters at the tip (D1, D2, D3).…”
Section: Introductionmentioning
confidence: 99%